O campo da produção acadêmica em Direitos Humanos: a influência das disputas de classe a partir da dinâmica relacional entre Estado, direito e educação - Ramos, Roberto Leonardo da Silva (2018)
The thesis examines the academic production in the field of human rights, specifically the master's degree dissertations defended in the ambit of the graduate program in Legal Sciences of the Paraíba Federal University from 2007 to 2015. It starts from the assumption that this production, in the field of legal sciences, constitutes a mechanism for the reproduction of the values of the ruling class, because it is permeated by class conflicts, constituting itself as an instrument of social control and maintenance of the occupants in the spaces of power. The purpose of this study is to analyze the influence of class disputes on academic production in law based on the relational dynamics between State, law and education, based on the categories of the legal field and symbolic power / legal-symbolic capital. It emphasizes the relational dynamics of the scientific and legal fields and its symbolic violence whose purpose is to cloak a society based on alienated relationships, which is strengthened by the actions of state agents. In this context, the official view of human rights, based on protecting the interests of vulnerable social agents and groups, is challenged by the ineffectiveness of this list of rights, constituting itself as a mechanism for strengthening alienation and symbolic violence. Notwithstanding this affirmation, a human rights perspective towards political emancipation is possible through the displacement of social agents from the margin to the decision-making center, through education and, above all, human rights education as an instrument of education and as a counter-consciousness of the existence of class disputes in the social space. For the purposes of analyzing the documentary corpus, the technique of content analysis is used as a technique for analyzing communications, using systematic procedures that allow the production of necessary inferences to identify what is revealed about a specific phenomenon.